Innovations for sustainable development: the need for transdisciplinary knowledge integration. (4th August 2014) - Zweekhorst, Marjolein B.M.; Broerse, Jacqueline E.W.; Bunders, Joske F.G.
In this article we argue that a transdisciplinary mode of knowledge integration, is key to the generation of sustainable agricultural innovations for small–scale, resource–poor farmers in developing countries. The concept and challenges of transdisciplinary research are described. We present a case study on the introduction of True Potato Seed in Bangladesh by a local non–governmental organization. The institutionalization process of a transdisciplinary approach to technology development within this organization is outlined. The case study is analyzed in relation to the identified main challenges for implementing transdisciplinary research. We conclude that application of a transdisciplinary approach throughout the innovation process requires changes in university curricula as well as organizational changes.